What's at stake of normalized relations between the United States and Iran - Matějková, Adéla; Druláková, Radka, 1973-; Matějka, Zdeněk, 1935 září 19.-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
This thesis tries to identify what's at stake of normalized relations between the United States and Iran since the Iranian revolution in 1979. The thesis tries to find out what are the key issues behind the failed relations between these two countries from the American point of view in order to determine whether normalized relations between these two countries can ever be achieved. It elaborates on four key characteristics of individual level analysis of foreign policy decision making applied on three key Presidents involved in foreign policy making towards Iran since 1979.
Vedoucí práce: Radka Druláková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses